The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1007/s11255-006-0075-5
|View full text |Cite
|
Sign up to set email alerts
|

The effect of ABO–Rh blood group determinants on urinary tract infections

Abstract: The concordance of UTI with blood group ARh+ may be due to the most seen of ARh+ phenotype in the investigated population. We suggest that before defining the relationships on genetical markers, it would be more reliable to correlate them with their local distributions in the population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 18 publications
1
2
1
Order By: Relevance
“…Many studies indicated a close relationship between ABO blood antigens and many diseases [24] [25] [26]. The relation of blood groups ABO with UTI found in many studies [27]. Our study with previous data [28] indicated blood groups ABO in relation to UTI depends on the epidemic region and bacterial genera.…”
Section: Resultssupporting
confidence: 79%
“…Many studies indicated a close relationship between ABO blood antigens and many diseases [24] [25] [26]. The relation of blood groups ABO with UTI found in many studies [27]. Our study with previous data [28] indicated blood groups ABO in relation to UTI depends on the epidemic region and bacterial genera.…”
Section: Resultssupporting
confidence: 79%
“…These findings may indicate the influence of A + and O + blood groups phenotypes on susceptibility to UT infection. 8 Comparing with the Turkish study, the ratios of this work are higher, indicating that the carriers of these blood groups are more susceptible within their ranges of ages (> 51)) for males and (10-30) for females. The variations between the ranges of ages of both males and females are related to anatomical factor ( the possibility of contamination because the urethra is very near to the vaginal wall and so women are more likely to get UT infection, or from sex act) or from the sexual intercourse and frequency of sex 17 , or other behavioral habits (not drinking enough fluids, cleanliness).…”
Section: Discussioncontrasting
confidence: 48%
“…First of all, we must refer to the congruence in the results of our study and those of the Turkish population. Both showed high proportions for people with UT infection who are holders of A + and O + blood groups distribution (36.6% and 31.7%, respectively in Turkish study 8 and 46.2% and 38.5%, respectively for the UTIs male patients of the current research). Knowing that the Turkish study was performed for patients as a mixed single group, while in this work a single group of females and another for males were used, separately.…”
Section: Discussionmentioning
confidence: 41%
See 1 more Smart Citation